Determination of generations X, Y, Z user preferences in the Russian mobile application market - E. S. Bozhenko; D. M. Nikolaeva; K. O. Svistunova (Вестник университета)
In the work, the authors reveal the user preferences of the mobile application market. The study is based on the Strauss–Howe generational theory. The mobile application market appears to be dynamic and fast-growing in an environment of exponential growth in consumer demand and a highly competitive environment. In the article, the authors classify and identify categories and subcategories of mobile applications based on their functional and value purpose. This classification formed the basis for determining the dependence based on the analysis of contingency matrices between the preference of the application for its purpose and the age category of the user, which made it possible to identify the relationship between generations of users and their choice of certain types of applications. The text provides a justification for the choice of certain applications on a daily basis by generations X, Y, Z. The relevance of the study lies in the fact that the authors examine a market, the rapid growth of which is conditioned by the global socio-economic situation. The information obtained during the analysis of user preferences of the Russian mobile application market can be used by specialists in determining the target audience of a digital product and developing marketing strategies.